Standardization of the Italian ALS-CBS™ Caregiver Behavioral Questionnaire - Aiello, Edoardo Nicolò; Solca, Federica; Greco, Lucia Catherine; La Tona, Antonino; Torre, Silvia; Carelli, Laura; Morelli, Claudia; Doretti, Alberto; Colombo, Eleonora; Messina, Stefano; Pain, Debora; Radici, Alice; et al. (Frontiers in Psychology, 2023)
Background. The present investigation aimed at testing the psychometrics and diagnostics of the Italian version of the Caregiver Behavioral Questionnaire (CBQ) from the ALS Cognitive Behavioral Screen (ALS-CBS™), as well as its case-control discrimination, in a cohort of non-demented patients with ALS. Methods. The caregivers of N=265 non-demented patients with ALS and N=99 healthy controls (HCs) were administered the CBQ and the Edinburgh Cognitive and Behavioural ALS Screen-Carer Interview (ECAS-CI). For N=98 patients, an in-depth behavioural/psychopathological assessment via the Frontal Behavioural Inventory (FBI), Dimensional Apathy Scale (DAS), State and Trait Anxiety Inventory-Form Y (STAI-Y) and Beck Depression Inventory (BDI) was also available. Factorial and construct validity, internal reliability and diagnostics against an abnormal ECAS-CI score were tested in patients. Case-control discrimination was explored through a logistic regression. Results. The CBQ was internally reliable (McDonald’s ω=.90) and underpinned by a simple, unidimensional structure; it converged with ECAS-CI, FBI and DAS scores and diverged from STAI-Y and BDI ones. A cut-off of ≤33 accurately detected abnormal ECAS-CI scores (AUC=.85), yielding optimal error- and information-based diagnostics. The CBQ was independent of demographic and disease-related variables and discriminated patients from HCs (p<.001). Discussion. The Italian version of the CBQ from the ALS-CBS™ is a valid, reliable, diagnostically sound and feasible screener for detecting frontotemporal-like behavioural changes in non-demented patients with ALS. Its adoption is thus recommended within clinical practice and research in the view of providing preliminary information on whether the administration of more extensive behavioural instruments is needed.